CULTURAL LIFE OF THE CITIES OF SOUTHERN UZBEKISTAN IN THE YEARS OF INDEPENDENCE (1991-2022) - Polvonov Kozimbek Naimovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes the cultural life of the cities of southern Uzbekistan during the years of independence. Kashkadarya region is considered one of the southern regions of the Republic of Uzbekistan, and during the years of independence, cultural and educational reforms accelerated in the cities of the region, folklore and folklore ensembles were organized under the departments of culture, events were held In order to popularize Uzbek folklore, libraries in the city area worked in a new way, and also In subsequent years, information was cited and analyzed that the introduction of new technical means into the life of society expanded the possibilities for obtaining information by the population.